Valuing nature attributes by the tourists : are there socio-demographic differences? - Oliveira, Paulo (2018)
This research studies if there are different valuations of nature attributes due to different socio-demographic characteristics of the individuals. We use the case of the Natural Park of Madeira and the valuation of its different attributes by the tourists to test if there are differences due to gender, age, education, and nationality; we control by the duration and number of previous visits to the destination. We use a probit model to see how socio-demographic characteristics of the tourists and different aspects of the trip affect the valuation given to 24 aspects of the Park and its organization. We conclude that males tend to value 12 of the aspects less and do not value any more than females. Age does not seem to affect the way individuals value the different aspects; the exception is the WC, which is more valued by the elderly. More educated people tend to value less the organizational aspects of the park and the services provided. British visitors value more than tourists from other nationalities 10 of the 24 aspects of the Park, while Germans tend to value less the services provided by the Park.